2020
DOI: 10.20448/journal.522.2020.61.65.71
|View full text |Cite
|
Sign up to set email alerts
|

Determination the Level of Physical Activity and Eating Behaviors of University Students

Abstract: The aim of this study was to determine the relationship between level of physical activity and eating behaviors of university students. 270 students attending to Inonu University in 2018-2019 academic year and volunteering were included in the study. A short form of the International Physical Activity Questionnaire (IPAQ-SF) and the Dutch Eating Behavior Questionnaire (DEBQ) were administered to the participants along with the socio-demographic information form. Data were analyzed by IBM statistics (SPSS, vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…Nonetheless, existing research on the effects of stress on physical exercise presented inconsistent findings. This study's result was in line with a statement by Düz & Tuba Aytekeli (2020), in which DEBQ subscales and MET scores had no significant association. Ingram et al (2020) concluded that relaxing lockdown restrictions result in a rapid boost of positive mood.…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, existing research on the effects of stress on physical exercise presented inconsistent findings. This study's result was in line with a statement by Düz & Tuba Aytekeli (2020), in which DEBQ subscales and MET scores had no significant association. Ingram et al (2020) concluded that relaxing lockdown restrictions result in a rapid boost of positive mood.…”
Section: Discussionsupporting
confidence: 91%
“…The men, when compared to the women, more often preferred high-intensity activities (Fagaras, Radu, & Vanvu, 2015). The lower level of physical activity among women is also confirmed by other researchers (Bartoszewicz, Oruc, 2019;Düz, & Aytekeli, 2020), however, there are research results, which show that sex does not fully determine the level of physical activity. High, medium and low levels of physical activity were similar for men and women (Grabowska,2020;Murphy, et al, 2019).…”
Section: Discussionsupporting
confidence: 56%
“…The studies among Spanish physical education students indicated that the students followed their diet (Mediterranean), while Romanian students pointed to the need to follow it in the context of sports (Chacón-Cuberos, Badicu, Zurita-Ortega, & Castro-Sánchez, 2018). Other studies did not confirm a significant correlation between eating patterns and the level of physical activity of students (Turkish universities), with men being more physically active than women (Düz, & Aytekeli, 2020).…”
Section: Discussionmentioning
confidence: 94%